2004
DOI: 10.1200/jco.2004.05.166
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Predict Complete Pathologic Response to Neoadjuvant Paclitaxel and Fluorouracil, Doxorubicin, and Cyclophosphamide Chemotherapy in Breast Cancer

Abstract: Our results suggest that transcriptional profiling has the potential to identify a gene expression pattern in breast cancer that may lead to clinically useful predictors of pCR to T/FAC neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
268
0
13

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(285 citation statements)
references
References 17 publications
4
268
0
13
Order By: Relevance
“…Gene 'signatures' or predictors have been devised for several chemotherapy regimens, including paclitaxel followed by fluorouracil, AC, AC/doxorubicindocetaxel and taxane only chemotherapy (Chang et al, 2003(Chang et al, , 2005bAyers et al, 2004;Hannemann et al, 2005;Cleator et al, 2006). Although these results are promising, the exceedingly small sample size and limitations with the current technology and analysis methods have so far precluded definitive conclusions (Brenton et al, 2005;Reis-Filho et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene 'signatures' or predictors have been devised for several chemotherapy regimens, including paclitaxel followed by fluorouracil, AC, AC/doxorubicindocetaxel and taxane only chemotherapy (Chang et al, 2003(Chang et al, , 2005bAyers et al, 2004;Hannemann et al, 2005;Cleator et al, 2006). Although these results are promising, the exceedingly small sample size and limitations with the current technology and analysis methods have so far precluded definitive conclusions (Brenton et al, 2005;Reis-Filho et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…The use of expression arrays to derive molecular profiles that are predictive of clinical outcome has received great attention in the last 5 years (van't Veer et al, 2005;Reis-Filho et al, 2006b), especially in the neoadjuvant setting (Davidson and Morrow, 2005). Predictive signatures for different neoadjuvant chemotherapy regimens have been reported by some investigators but with less success by others (Chang et al, 2003;Ayers et al, 2004;Cleator and Ashworth, 2004;Chang et al, 2005a;Hannemann et al, 2005;Iwao-Koizumi et al, 2005;Modlich et al, 2005;Rouzier et al, 2005;Dressman et al, 2006;Reis-Filho et al, 2006b). Although some of these results are promising, issues related to the instability of mRNA, experimental design and data analysis have led many to call into question the validity of current approaches (Ransohoff, 2004;Brenton et al, 2005;Ioannidis, 2005;Reis-Filho et al, 2006b).…”
mentioning
confidence: 99%
“…It is now well documented that NFAT proteins are also present in non-immune cells and regulate a variety of signaling pathways involved in cell growth and development (Baksh et al, 2002;Chuvpilo et al, 2002;Mancini and Toker, 2009;Muller and Rao, 2010). Importantly, members of the NFAT family, in particular NFAT5, have recently been involved in the migratory capacity of breast cancer cells (Jauliac et al, 2002;Ayers et al, 2004;Yoeli-Lerner et al, 2005;Mancini and Toker, 2009;Fougere et al, 2010;Muller and Rao, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, sequential taxane and anthracycline-containing regimes are used most commonly in the neoadjuvant setting. Thus, Ayers et al 11 tried to identify a 74-gene signature associated with pCR to sequential paclitaxel plus 5-fluorouracil (5-FU)/doxorubicin/cyclophosphamide (FAC), and Hess et al 12 reported using a 31-gene classifier as a predictor of pCR to the same regimen with similar diagnostic accuracy.…”
mentioning
confidence: 99%
“…In the studies by Ayers et al 11 and Hess et al, 12 tumor samples were obtained with fine-needle aspiration (FNA) before patients received neoadjuvant chemotherapy. Because, currently, patients usually undergo core-needle tumor biopsy (eg, Mammotome; HH Ethicon Endosurgery, Johnson and Johnson Company, Langhorne, Penn) before they receive neoadjuvant chemotherapy, and a sufficient sample volume for the gene expression assay is easily obtainable, we believe that core-needle samples constitute a better source for the assay than FNA samples.…”
mentioning
confidence: 99%